2014
DOI: 10.1590/s0104-12902014000400003
|View full text |Cite
|
Sign up to set email alerts
|

Distance effects on the accessibility to emergency departments in Portugal

Abstract: Distance patients have to travel has shown to influence demand for several health services. Our work looks at this effect on the utilization of Emergency Departments (ED) in Portugal. We build upon previous works by taking into account both the severity of emergency visits and the type of ED and by including a set of other variables that have shown to influence ED utilization. Overall, we find distance--elasticity for emergency care that ranges from -1 to -2 (a 10% increase in distance to ED results in a 10-20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 20 publications
(19 reference statements)
4
27
0
2
Order By: Relevance
“…For instance, our study suggests a negative income gradient where patients reporting middle and high-income households were associated with fewer ED visits compared with those who reported lower income. This is consistent previous studies that showed lowerincome status is associated with higher ED utilization (Vaz et al 2014). Having insurance eligibility was associated with more ED visits in our study.…”
Section: Discussion Of Resultssupporting
confidence: 93%
“…For instance, our study suggests a negative income gradient where patients reporting middle and high-income households were associated with fewer ED visits compared with those who reported lower income. This is consistent previous studies that showed lowerincome status is associated with higher ED utilization (Vaz et al 2014). Having insurance eligibility was associated with more ED visits in our study.…”
Section: Discussion Of Resultssupporting
confidence: 93%
“…However, it is collected using systematic methods across all hospitals and these methods have not changed over the study period. Therefore, the greatest risk is likely to be consistent over or under-estimation at a national level rather than in comparisons across hospitals or time 46 47…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis may not have captured changes in population need for emergency services in a region. It is possible that reconfiguration may have reduced overall expressed need for ED services within parts of a region because some patients who would previously have travelled to an ED and been admitted may no longer do so because of the extra burden of travel 46 47. This might offset the increased need for beds in the hospitals with post-reconfiguration EDs.…”
Section: Discussionmentioning
confidence: 99%
“…Cuidados representados por procedimentos não invasivos como a imobilização em prancha longa 13 . Concomitantemente com os avanços tecnológicos a sociedade ao usufruí-los expôs-se a um maior grau de risco, o que tornou a implementação do suporte avançado à vida (SAV), necessidade 14 . Necessidade socioambiental que associa as pessoas ao Estado, ou seja, configura-se no cumprimento do direito à vida pelos representantes do Estado por meio do acesso aos serviços de saúde 15 .…”
Section: Revisão De Literaturaunclassified
“…Iminência que exige profissionais em constante aperfeiçoamento, acrescidos por uma permanente gestão de pessoas e materiais 30 . Primeiramente, para viabilizar o cuidado com a saúde e a segurança de quem cuida, os próprios profissionais, para posteriormente permitir que estes possam desenvolver constantemente a investigação clínica e a tomada de decisão no socorro aos pacientes 14 . Socorro que deve ser acionado pelas pessoas que se encontram em situação de acometimento agudo da saúde, ou melhor, vivenciam uma crise.…”
Section: Atendimento Móvel De Urgência: Gestão De Serviçounclassified